2019
DOI: 10.3390/su11184878
|View full text |Cite
|
Sign up to set email alerts
|

Managerial Overconfidence and Cost Behavior of R&D Expenditures

Abstract: This study examines the impact of a CEO’s confidence level on decisions regarding research and development (R&D) expenditures. R&D is an important part of a company’s strategy for achieving long-term sustainable growth. However, due to its discretionary nature, some CEOs choose to reduce R&D costs to enhance short-term performance. In other words, R&D cost behavior may vary depending on CEO characteristics. This study examines whether, in an effort to improve their firm’s future performance, CE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
15
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 33 publications
(84 reference statements)
3
15
0
4
Order By: Relevance
“…The results imply that as CSR activities increase, long-term performance decreases. However, when we introduce an interaction term, CSR × OC, which combines the CSR dummy (if CSR > 0, then CSR_D = 1, otherwise 0) with OC ranks (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) as in models 3 and 4, the results are totally different. The relationship between CSR and AAR turns to positive and significant (p-value < 5%) in model 3.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The results imply that as CSR activities increase, long-term performance decreases. However, when we introduce an interaction term, CSR × OC, which combines the CSR dummy (if CSR > 0, then CSR_D = 1, otherwise 0) with OC ranks (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) as in models 3 and 4, the results are totally different. The relationship between CSR and AAR turns to positive and significant (p-value < 5%) in model 3.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, if firms face financial constraints with regard to engaging in CSR activities, rigorous CSR activities could be harmful to their long-term performance. We examine the long-term performance of CSR activities initiated by overconfident CEOs, considering financial constraints.Prior research on the impact of a CEO's emotional bias (optimism, loss aversion, overconfidence) and other self-serving bias on corporate strategic decisions included financing decision [16], investments [17], dividend payment [18], cost behavior, and R&D expenditure [19]. This paper tries to examine the impact of CEOs' overconfidence level on CSR activities for the first time.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Overconfidence is one of the key manifestations to show the irrationality of corporate executives, which refers to the psychological deviation that people tend to overestimate their success probability and underestimate their failure probability [65,66]. Studies have shown that overconfidence varies among individuals of different gender, age and educational background.…”
Section: Famous University Experience Overconfidence and Corporate Pmentioning
confidence: 99%
“…However, recent empirical research demonstrates asymmetry in cost behavior -in other words, that costs increase more rapidly with activities than they decrease -which has been termed "cost stickiness" [3]. Recent studies have examined asymmetric cost behavior as a function of managerial deliberate cost adjustment [3][4][5], managerial optimism or pessimism [6], earnings management incentives [7,8], agency problem [9], earnings forecasts [10], capacity utilization [11], unemployment [12], product market competition [13], corporate social responsibility [14], conservatism [15], and whether or not the costs are related to the core operations of a firm [16].…”
Section: Introductionmentioning
confidence: 99%